Translating Discourse with Chinese Characteristics Guided by High and Low Context Cultures Theory: A Case Study of the Series of Understanding Contemporary China - Zihang Guo; Chili Li (Universitas Sebelas Maret, 2025)
In the 21st century, China’s developing international stature has sparked increased global interest in its governance principles and practices. This has necessitated the effective translation of Chinese political literature to facilitate cross-cultural understanding. This study aims to explore the translation strategies of Chinese political discourse, focusing on the series of Understanding Contemporary China through the lens of Edward T. Hall’s high-low context culture theory. The research takes a qualitative approach, employing contrastive analysis methodology. It investigates a total of 98 Chinese expressions characterized by Chinese rich cultural connotations, drawn from the selected series. The foreignization strategy seeks to preserve the cultural integrity of the source language through literal translation supplemented by explanatory annotations. In contrast, domestication reinterprets the original expressions to align with the cultural norms of the target language, employing free translation and semantic adaptation. This study enhances our comprehension of translation dynamics between high-context and low-context cultures, while simultaneously providing critical perspectives on the international propagation of Chinese political philosophy. In doing so, it fosters more effective intercultural dialogue and contributes to the reduction of cross-cultural misinterpretations.